Tantangan Pengembangan Kemampuan Berpikir Kritis Siswa dalam Implementasi Kurikulum Merdeka di SDN Pengambangan 9 - R, Irayanti; Maharani, Jihan Milanda; Aniyah, Naila; Kholillah, Siti; Pratiwi, Diani Ayu (Lembaga Yasin AlSys, 2025)
This article analyzes the low critical thinking skills of students in the implementation of the Merdeka Curriculum at SDN Pengambangan 9. This study aims to identify the factors that influence students' thinking activities. Through interviews with teachers, it was found that although the Merdeka Curriculum aims to encourage students to think independently and actively in the learning process, many students are, in fact, less active, not accustomed to working in groups, and tend to be passive in expressing their opinions. Contributing factors include the rapid transition of the curriculum, limitations in infrastructure such as projectors and internet connectivity, and teachers' uneven understanding in applying the new approach. Furthermore, the P5 project, which aims to build character, has created new challenges, particularly in terms of costs and parental participation. Although some teachers acknowledge that the Merdeka Curriculum helps students focus more on specific material, which impacts academic achievement, various obstacles still need to be addressed. The school routinely holds community learning training (kombel) and encourages teachers to attend workshops funded by the BOS (School Operational Assistance). The results of this study recommend improvements in learning facilities, more intensive teacher mentoring, and evaluations of character-based projects to make them more adaptive to school conditions.